Analysis of All Risk Property Insurance Product Development Strategy from the Perspective of Sharia Strategic Management at PT Jasindo Syariah Medan Branch - Indra Rizki Hasibuan; Maidalena; Nurwani (LP2M IAIN Palopo, 2025)
The Islamic insurance industry in Indonesia has shown significant growth, but challenges in developing specialized products such as Property All Risk (PAR) insurance remain high, particularly in terms of sharia compliance and product innovation. This study aims to analyze the PAR insurance product development strategy at PT Jasindo Syariah Medan Branch through a sharia strategic management perspective. The method used is a descriptive qualitative approach with data collection techniques such as interviews, observation, and documentation. The results show that the product development strategy is carried out strictly in accordance with sharia principles by selecting insurance objects based on halal-haram, adjusting benefits based on local conditions, and implementing standard policy wording from regulators. A value-based strategy, collaboration with Islamic institutions, and a focus on service are the main differentiations amidst limited innovation due to uniform product regulations. However, low public literacy, minimal branch autonomy, and limited product innovation are the main obstacles. This study concludes that the strategy of PT Jasindo Syariah Medan Branch is in accordance with the principles of sharia strategic management, but needs to be strengthened in terms of market education and operational flexibility to increase competitiveness.